Selecting the appropriate design in biomedical research: experimental studies. Part II - Raúl Aguilera Eguía; Ángel Roco Videla; Olga Patricia López Soto; Brenda Herrera Serna; Héctor Fuentes Barria; Mariana Melo Lonconao (Medisur)
This document is the second part of a series focused on the prevalent research designs in clinical epidemiology, and is especially dedicated to the critical importance of experimental studies in the health care evolution. Considerations are issued from the historical evolution and theoretical foundations, to the practical implementation of experimental designs, with a particular focus on randomized clinical trials, for their robustness in demonstrating causal relationships and influence in optimizing clinical decisions. Fundamental ethical criteria, including informed consent and ethical review, are also addressed, highlighting their indispensable role in the protection of study subjects and the overall integrity of research. The aim is to provide health professionals and students with in-depth knowledge and practical skills for the ethical and effective application of these experimental methods, thus contributing to raising the standards of medical care and scientific progress.